Improving income protection for the elderly poor in Ecuador - César A. Amores L.; H. Xavier Jara (University of Essex, Institute for Social and Economic Research (ISER), 2018)
A series of social benefits targeting vulnerable groups, such as the elderly population, has been implemented in Ecuador over the last few decades. Elderly adults living in vulnerable conditions and not affiliated with social security are entitled to noncontributory pension assistance under the Human Development Transfer program. However, over one quarter of old-age beneficiaries still live in poverty and the recent fall in oil prices has put increasing pressure on government expenditures to deliver such schemes. This paper aims to assess the current needs of old-age adults based on expenditure data, and makes use of microsimulation techniques to evaluate the effect of covering those needs through an increase in pension assistance. Our results show that increasing pension assistance to match the level of the poverty line in Ecuador would reduce elderly poverty by 40% and would take 18% of old-age beneficiaries out of poverty. We analyze the effect of additional hypothetical reforms and discuss the importance of using microsimulation techniques, in particular to assess the effect of budget neutral reforms in a macroeconomic environment with low oil prices.
Keywords: I32; I38; H24; D13; 330; Pension Assistance; Human Development Transfer; Microsimulation